2012
DOI: 10.1139/x11-165
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte response to forest canopy treatments within the riparian zone of high-elevation small streams

Abstract: Riparian buffer strips are increasingly used to mitigate disturbance effects on terrestrial biota found adjacent to streams, yet it is unclear how the effects of canopy treatment (clear-cut, buffer, or intact forest) will interact with pre-existing stream–upland gradients. We questioned whether proximity to the stream would influence bryophyte richness and whether the effects of canopy treatment on bryophyte composition and functional group representation would differ along the stream–upland gradient. Bryophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Feather mosses, such as Hylocomium splendens, Pleurozium schreberi, P. crista‐castrensis and the liverwort P. pulcherrimum , were identified as indicators for unharvested controls and are known to be associated with intact coniferous forest (Caners et al., ; Shields et al., ). The substantial declines in bryophyte richness in clear‐cuts that we observed initially support previous results from other forest systems in North America (Baldwin et al., ; Dovčiak et al., ) and northern Europe (Hylander & Weibull, ; Rudolphi, Jonsson, & Gustafsson, ). These effects of harvesting can be attributed to direct physical damage to both the forest floor and associated substrates (Fenton, Frego, & Sims, ) and to changes in microclimate, such as increased temperature, reduced humidity and increased light.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Feather mosses, such as Hylocomium splendens, Pleurozium schreberi, P. crista‐castrensis and the liverwort P. pulcherrimum , were identified as indicators for unharvested controls and are known to be associated with intact coniferous forest (Caners et al., ; Shields et al., ). The substantial declines in bryophyte richness in clear‐cuts that we observed initially support previous results from other forest systems in North America (Baldwin et al., ; Dovčiak et al., ) and northern Europe (Hylander & Weibull, ; Rudolphi, Jonsson, & Gustafsson, ). These effects of harvesting can be attributed to direct physical damage to both the forest floor and associated substrates (Fenton, Frego, & Sims, ) and to changes in microclimate, such as increased temperature, reduced humidity and increased light.…”
Section: Discussionsupporting
confidence: 91%
“…America (Baldwin et al, 2011;Dovčiak et al, 2006) and northern Europe (Hylander & Weibull, 2012;Rudolphi, Jonsson, & Gustafsson, 2014). These effects of harvesting can be attributed to direct physical damage to both the forest floor and associated substrates (Fenton, Frego, & Sims, 2003) and to changes in microclimate, such as increased temperature, reduced humidity and increased light.…”
Section: Higher Levels Of Retention More Effectively Conserve Bryopmentioning
confidence: 99%
“…Bryophytes are strongly associated with wet ground; for example Baldwin et al. () found bryophyte richness was highest in areas closest to streams. They also do well on substrates with a concave form, such as moist ground, wet ground and stream channel margins, which are characterised by being closer to the ground water table, as compared to convex substrates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Conceivably, semi-aquatic bryophytes may provide the most appropriate indices for anthropogenic change in many ecosystems since they are located at the terrestrial-aquatic interface, and are therefore influenced by changes occurring in both terrestrial and aquatic ecosystems. Timber harvest effects that may prove detrimental to bryophyte health include increased erosion and sediment, altered stream flow regimes, microclimate (including light availability and air and stream temperature) and nutrient regimes [11][12][13][14][15][16][17][18][19][20][21]. Given bryophyte sensitivity to disturbance, forest management including clearcutting or thinning (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of recent primary literature concerning the effect of climatic alterations and/or timber harvest impacts on bryophytes suggested that the major-ity of studies have utilized community characteristics such as percentage cover, abundance, and various parameters of species richness and composition as measures of bryophyte response [4,6,[18][19][20][21]24,25,[27][28][29][30][31][32][33]. Of the studies that have addressed physiological and morphological responses of bryophyte species to altered climate conditions, many have focused on increased temperatures and radiation levels in Artic and sub-Artic ecosystems [34][35][36], or the response of bryophytes to increased levels of nutrients such as Nitrogen and Phosphorus [37,38].…”
Section: Introductionmentioning
confidence: 99%